Enforcement Of Environmental Laws Regarding Electric Power Generation Business Activities In The Nickel Industry That Do Not Meet Business Licensing Commitments In Indonesia - Hafiza, Hafiza; Widowaty, Yeni; Putra, Ilham Setiawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
One of the functions of the high-risk-based business licensing law is to prevent or overcome environmental problems. Therefore, fulfilling business licensing commitments before operating is crucial for environmental protection, especially in high-risk business activities. This research aims to examine Environmental Law Enforcement Against the Coal Steam Power Plant (PLTU Batubara) owned by PT. Naga Virtue Nickel Industry (PT. VDNI) in Konawe Regency needs to fulfill its business licensing commitments. The approach used in this research is an empirical normative legal approach. The research results show that between 2016 and April 20, 2020, the coal PLTU PT. VDNI did not have its own Electricity Supply Business License (IUPTLS) and did not submit reports on its electricity supply business activities then. Apart from that, PT. Coal Power Plant PT. The VDNI is not legally valid because it was issued by the Southeast Sulawesi Province ESDM Service, not the Minister through the Director General or an accredited Technical Inspection Institute, and did not install Continuous Emission Monitoring Systems (CEMS) technology in coal mining. Oil-fired power plant. Coal Power Plant PT. VDNI fulfilled its IUPTLS commitment on April 21, 2020. Even though PT. VDNI and Person in Charge PT. VDNI violated the law; no sanctions were received from the regional or central governments.